19 × 1 high power pump combiner with large input core diameter. (19th February 2021) - Zhang, Hui; Lei, Chengmin; Li, Zhixian; Chen, Zilun
Abstract: In this paper, we investigate a 19 × 1 tapered fiber bundle (TFB) pump combiner for high power fiber lasers theoretically and experimentally, based on the twist method. Theoretically, we analyze the influence of the taper length, taper ratio and twist angle on the performance of a 19 × 1 TFB combiner by using the beam propagation method. Then, a 19 × 1 all-fiber combiner is fabricated experimentally, with input fibers and output fiber having core/clad diameter of 220/242 μ m (numerical aperture (NA) = 0.22) and 30/600 μ m (NA = 0.06/0.46) respectively. The transmission efficiency of each port is higher than 98.6% and the average efficiency of all 19 ports is 99.3%. The combiner achieved an output power of 1.5 kW with transmission efficiency of 99.3% when tested with four ports of 976 nm laser diode. To our best knowledge, this is the first time that 220/242 μ m (NA = 0.22) multimode fibers act as the pump fibers of a 19 × 1 end-pumping combiner.